Effects of chlorination on microplastics pollution: Physicochemical transformation and chromium adsorption. (15th April 2023) - Miao, Manhong; Yu, Bingqing; Cheng, Xuhua; Hao, Tianwei; Dou, Yuanyuan; Zhang, Min; Li, Yao
Abstract: The large number of microplastics (MPs) that appear in the environment has drawn much attention. Few studies, however, have examined the transformation of MPs in water treatment processes and their effects on environmental pollutants. In this study, the alteration of the physicochemical characteristics of polyethylene and thermoplastic polyurethane upon chlorination, as well as the influence of this alteration on contaminants, were investigated. The findings indicated that microplastics underwent significant morphology and O-functional groups changes during chlorination. It is noteworthy that the mechanisms controlling the chlorination treatment of the two MPs are clearly different. The results of aggregation and adsorption experiments showed that the chlorination treatment enhanced the aggregation ability of the MPs in brine and their interaction with Cr(VI). The present discoveries further suggested that water treatment could alter the migration capacity of microplastics and the distribution of contaminants in the aqueous environment by altering the adsorption of microplastics to the contaminants. Graphical abstract: Image 1 Highlights: The surface function of MPs was altered by chlorination, leading to fracture. TPU was more sensitive to chlorination than PE. Chlorination has a greater effect on the motion of PE in salt water than TPU. The chlorination of PE and TPU increased their capacity to adsorb Cr(VI).